The Challenges that English Teachers Face in the Employment of the Evaluation Matrix in Classes for Students with Learning Difficulties - Mohammad Abedrabbu Alkhawaldeh; Mohamad Ahmad Saleem Khasawneh (Journal La Edusci, 2021)
The current study aimed at identifying the challenges that English teachers face when they employ the evaluation Matrix in classes for students with learning difficulties. The study followed the descriptive-analytical method. A questionnaire was designed to meet the study objectives. the study sample consisted of 136 English teachers of the primary education level in public schools in the city of Irbid. The findings revealed that the challenges that English teachers face in employing the evaluation Matrix in classes for students with learning difficulties came with a very high degree, they also revealed the absence of differences with statistical significance between the responses of the sample attributable to the variables of gender and experience years. Furthermore, the findings showed the presence of statistically significant differences between the responses of the sample attributable to the variable of academic qualification.